2015
DOI: 10.3389/fphys.2015.00297
|View full text |Cite
|
Sign up to set email alerts
|

In vitro osteogenic and odontogenic differentiation of human dental pulp stem cells seeded on carboxymethyl cellulose-hydroxyapatite hybrid hydrogel

Abstract: Stem cells from human dental pulp have been considered as an alternative source of adult stem cells in tissue engineering because of their potential to differentiate into multiple cell lineages. Recently, polysaccharide based hydrogels have become especially attractive as matrices for the repair and regeneration of a wide variety of tissues and organs. The incorporation of inorganic minerals as hydroxyapatite nanoparticles can modulate the performance of the scaffolds with potential applications in tissue engi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 45 publications
1
29
0
1
Order By: Relevance
“…One study demonstrated that vascular endothelial growth factor (VEGF) gene could promote odontogenic differentiation in DPSCs in vitro [14] while another identified that DPSCs undergo osteogenic differentiation through the NF-kB signaling pathway [15]. DPSCs had the ability to differentiate toward both odontogenic and osteogenic lineages in presence of a carboxymethyl cellulose-hydroxyapatite hybrid hydrogel [16]. Furthermore, medium modification with bone morphogenetic protein 2 was shown to stimulate odontogenic differentiation and formation of an osteo-dentin matrix [17].…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that vascular endothelial growth factor (VEGF) gene could promote odontogenic differentiation in DPSCs in vitro [14] while another identified that DPSCs undergo osteogenic differentiation through the NF-kB signaling pathway [15]. DPSCs had the ability to differentiate toward both odontogenic and osteogenic lineages in presence of a carboxymethyl cellulose-hydroxyapatite hybrid hydrogel [16]. Furthermore, medium modification with bone morphogenetic protein 2 was shown to stimulate odontogenic differentiation and formation of an osteo-dentin matrix [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the vascularization could guide MSCs migration from perivascular region to the inflammatory loci [62]. Having multipotential and self-renewal properties, MSCs such as dental pulp stem cells (DPSCs) differentiate into odontoblasts, fibroblasts, endothelial cells, and neural cells [63][64][65][66][67][68]. The vascularization is supported by the angiogenic signaling molecules, vascular endothelial growth factor (VEGF), basic fibroblast growth factor (bFGF), and TGF-β which are released from injured pulp cells, endothelial cells, and ECM [69,70].…”
Section: Biologic Defense Mechanism On Pulp-dentin Tissuementioning
confidence: 99%
“…The wound‐healing capabilities of CMC may be further enhanced through implantation of nanoparticles . It has also used in drug delivery and tissue engineering applications . CMC is utilized in these ways by exploiting its properties as a biodegradable and superabsorbent material, which depend greatly on the degree of crosslinking.…”
Section: Introductionmentioning
confidence: 99%